Regioselective Synthesis of 1, 4, 5‐Trisubstituted‐1, 2, 3‐Triazoles from Aryl Azides and Enaminones. Issue 33 (15th August 2019) - De Nino, Antonio; Algieri, Vincenzo; Talllarida, Matteo A.; Constanzo, Paola; Pedrón, Manuel; Tejero, Tomás; Merino, Pedro; Maiuolo, Loredana
Abstract : A total regioselective synthesis of 1, 4, 5‐trisubstituted‐1, 2, 3‐triazoles from aryl azides and enaminones is reported. The use of an ionic liquid in the presence of water and trimethylamine is crucial for the progress of the reaction. The process, consisting of a cascade starting with a water‐promoted 1, 3‐dipolar cycloaddition (in agreement with DFT calculations) followed by a base‐promoted retro‐aza‐Michael reaction, shows a completely different reactivity to previously reported base‐promoted reactions between enaminones and sulfonyl azides only leading to disubstituted triazoles. Such reactivity, reported herein, allows preparation of trisubstituted triazoles in a complete regioselective way. Abstract : Total regioselective synthesis of 1, 4, 5‐trisubstituted‐1, 2, 3‐triazoles has been achieved from aryl azides and enaminones. The reaction consists of a cascade starting with a water‐promoted 1, 3‐dipolar cycloaddition followed by a base‐promoted retro‐aza‐Michael reaction. DFT calculations support the mechanism.